DOI: 10.11606/d.11.2011.tde-29112011-150451
|View full text |Cite
|
Sign up to set email alerts
|

Aditivos (ionóforos, antibióticos não ionóforos e probióticos) em dietas com altos teores de concentrado para tourinhos da raça Nelore em terminação

Abstract: Additives (ionophores, non ionophores antibiotics and probiotics) for Nellore bulls fed high concentrate diets Two trials were conducted at the ESALQ/USP Animal Science Department experimental feedlot to evaluate the effect of different feed additives in feedlot finished cattle. The animals were fed with 78.1% ground corn, 12% Tifton hay, 6% sugarcane molasses, 2.5% mineral, 1.4% urea and the respective additives. The first trial had 134 Nellore bulls with an average of 24 months and 330 Kg of initial body wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 72 publications
(130 reference statements)
2
7
0
Order By: Relevance
“…The carcass yield and final weight of confinement weight data of the present study corroborate with those found by Sitta (2011), in Nelore steers finished with MO and with MO+VI. However for the same fat thickness found no significant difference.…”
Section: Período De Confinamentosupporting
confidence: 91%
See 3 more Smart Citations
“…The carcass yield and final weight of confinement weight data of the present study corroborate with those found by Sitta (2011), in Nelore steers finished with MO and with MO+VI. However for the same fat thickness found no significant difference.…”
Section: Período De Confinamentosupporting
confidence: 91%
“…Sitta (2011) states that the VI has a greater ability to ruminal microbiota manipulation, taking with it a better control on lactate production and a decrease in methane production, generating lower energy losses, explaining the fact that the treatments VI get better results in this study.…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…In a literature review, Sitta (2011) also demonstrated that the use of monensin for bovines in feedlot reduced on average 6.33% of DDMI and 1.8% of ADG, and improved FC by 5.64%. Conversely, salinomycin use reduced DDMI by 3.15%, increased ADG by 1.19%, and increased FC by 4.44%.…”
Section: Resultsmentioning
confidence: 95%